2020
DOI: 10.1016/j.heliyon.2019.e03077
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto's thyroiditis attenuates progression of papillary thyroid carcinoma: deciphering immunological links

Abstract: Although some studies have investigated the clinicopathologic relationships between papillary thyroid carcinoma (PTC) and Hashimoto's thyroiditis (HT), there is still no clear understanding of differences in tumor immune microenvironment for PTC with coexisting HT and HT effect on PTC progression. The aim of this study was to clarify immune-mediated mechanisms of coexisting HT, which might influence PTC progression. 30 patients with histologically confirmed conventional-type PTC and 30 patients with PTC and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
1
12
0
2
Order By: Relevance
“…The authors reported the frequencies of PTC and undifferentiated thyroid cancer were 6% and 2%, respectively, among all patients (14). The possibility of concurrence of HT, PTC, and MTC depends on some gene rearrangements (5,6,9,13). Besides these synchronous occurrences, HT has been introduced as playing a protective role against PTC progression (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported the frequencies of PTC and undifferentiated thyroid cancer were 6% and 2%, respectively, among all patients (14). The possibility of concurrence of HT, PTC, and MTC depends on some gene rearrangements (5,6,9,13). Besides these synchronous occurrences, HT has been introduced as playing a protective role against PTC progression (15).…”
Section: Discussionmentioning
confidence: 99%
“…The source of this cancer is follicular thyroid cells and PTC is known as the seventh most common cancer among women and the secondfastest-growing tumor among men (1,4). The risk factors of PTC has been documented as exposure to ionizing radiation, female gender, smoking, obesity, dietary iodine excess, alcohol, dietary nitrates, diabetes, and genetic factors (5). PTC is related to exclusive mutations, including BRAF V600E, RAS, and chromosomal rearrangements leading to the expression of tyrosine kinase receptors such as RET, NTRK, and ALK (2).…”
Section: Introductionmentioning
confidence: 99%
“…Рефлюкс асоційований зі зменшенням рН, зміною експресії карбоангідрази ІІІ і спричиняє розвиток запалення, що може сприяти пух линній трансформації та впливати на реалі зацію протипухлинної імунної відповіді [2,7,8]. Ключовими клітинами протипухлинного імунітету є Т-цитотоксичні лімфоцити (CD8 + ) [9,10]. Закономірно, що щільність інфільтрації пухлин CD8 + -лімфоцитами, позитивно корелює з виживаністю хворих на РГ [8,11].…”
Section: вступunclassified
“…Показано, що зростання щільності інфільтрації пухлини CD3 + -і CD8 + -лімфоцитами було асоційоване з покращенням прогнозу перебігу пухлинного процесу у пацієнтів з карциномами голови та шиї [14]. Також відомо, що попереднє запалення та лімфоїдна інфільтрація можуть впливати на прогноз та ефективність лікування хворих з іншою онкологічною патологією [4,10,14]. Виявлені в роботі морфологічні зміни при ЛФР є досить закономірними з огляду на рівень рН та дію ферментів.…”
Section: результати та їх обговоренняunclassified
“…With changes in lifestyle and improvements in detection technology, the incidence of this disease has been increasing, and the age of onset is mainly 30-50 years of age, with significantly more women than men impacted by HT (men vs. women: 1:4-20) (3,4). Studies have shown that the prevalence of papillary thyroid cancer in HT patients is higher than that of the normal population, suggesting that HT may be a risk factor for thyroid cancer (5). Some scholars have even proposed that HT is a precancerous lesion of papillary thyroid cancer (6).…”
Section: Introductionmentioning
confidence: 99%